Penerapan Algoritma K-Medoids Dalam Klasterisasi Penyebaran Tempat Ibadah Di Sumatera Utara - Didik Maulana; SIti Sundari; Khairunnisa (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
A place of worship is a public facility built to meet the needs of religious people in carrying out the obligation to worship God Almighty. Places of worship in North Sumatra Province include mosques, churches, monasteries, temples, and temples. The increasing number of congregations can result in inadequate capacity for places of worship so that people have to find other places of worship. Until now, the government and the surrounding community have been trying to determine the location of the construction of a strategic place of worship, which can be used by tourists in terms of worshipping God. Considering that the government has not carried out mapping to find out which areas have been built or have not been places of worship. In order for the process to be more objective, of course, tools are needed, namely an information system that can process existing data into information.The technique used in data processing is data mining. The method used is K-Medoids. Implementation of the k-medoids algorithm that is performed by using Microsoft Visual Basic 2010 The results obtained that data on the distribution of places of worship in North Sumatra for 2011 to 2020 which were divided into 5 clusters where in cluster 1 there were 44 members, cluster 2 totaled 23 members, cluster 3 amounted to 49 members, cluster 4 amounted to 64, and cluster 5 amounted to 150.Keywords: Cluster, K-Medoids, Worship Place, Microsoft Visual Studio